Effect of piperine on the bioavailability and pharmacokinetics of rosmarinic acid in rat plasma using UPLC-MS/MS. (1st February 2018) - Yang, Jun-Hui; Mao, Kun-Jun; Huang, Ping; Ye, Yin-Jun; Guo, Hua-Shan; Cai, Bao-Chang
Abstract: 1. The purpose of the present study was to investigate the effect of piperine (PP) on the pharmacokinetics of rosmarinic acid (RA) in rat plasma and to determine whether PP could enhance the oral bioavailability of RA via inhibition of its glucuronidation. 2. The pharmacokinetic profiles of RA between oral administration of RA (50 mg/kg) alone and in combination with different oral dose PP (20, 40, 60, and 80 mg/kg) to rats were investigated via a validated UPLC/MS/MS method. 3. The AUC and C max of RA were significantly increased in combination with different dose PP dose dependently, especially in the presence of 60 and 80 mg/kg PP ( p < 0.01). The relative bioavailability of RA in the presence of 20, 40, 60, and 80 mg/kg PP was 1.24-, 1.32-, 2.02-, and 2.26-folds higher, respectively, compared with the control group given RA alone. Compared with RA, the pharmacokinetic modulations of RA glucuronide were even more apparent, and the glucuronidation of RA was remarkedly inhibited. 4. This study demonstrated that PP significantly improved the in vivo bioavailability of RA partly attributing to the inhibition of gut and hepatic metabolism enzymes of RA.